THE PASSIONS AND THE FORMS OF LIFE OF DAENERYS TARGARYEN IN GAME OF THRONES - Souza, Kélica Andréa Campos; Câmara, Naiá Sadi (Laboratório Editorial FCL-UNESP, 2015)
The North-American serial fictional narratives have been attracting more and more space among Brazilian people due to cable TV popularization and Internet consumer expansion. This kind of cultural product is one of the main means responsible for spreading and determining values, behaviors and new forms of life. The TV series Game of Thrones was chosen as the corpus of this paper in order to identify the new forms of life that have been transmitted to society, motivated by a good public support and also because of the presence of well-constructed and complex female characters. By analyzing Daenerys Targaryen’s path, female actor whose forms of life undergo a very significant change in the plot, her narrative and passional paths will be approached with the objective of identifying the forms of life attributed to her as well as the actancial, thematic and pathemic roles invested in her. The methodological and theoretical reference for this paper will be based on the Greimassian semiotics, more specifically the narrative and discursive level of the generative process of meaning, in addition to the theoretical precepts about passions and forms of life.